Loss of PBAF promotes expansion and effector differentiation of CD8+ T cells during chronic viral infection and cancer - Arjun Kharel; Jian Shen; Ryan Brown; Yao Chen; Christine Nguyen; Donia Alson; Theresa Bluemn; Jie Fan; Kexin Gai; Bin Zhang; Matthew Kudek; Nan Zhu; et al. (Cell Reports, 2023)
Summary: During chronic viral infection and cancer, it has been established that a subset of progenitor CD8+ T cells continuously gives rise to terminally exhausted cells and cytotoxic effector cells. Although multiple transcriptional programs governing the bifurcated differentiation trajectories have been previously studied, little is known about the chromatin structure changes regulating CD8+ T cell-fate decision. In this study, we demonstrate that the chromatin remodeling complex PBAF restrains expansion and promotes exhaustion of CD8+ T cells during chronic viral infection and cancer. Mechanistically, transcriptomic and epigenomic analyses reveal the role of PBAF in maintaining chromatin accessibility of multiple genetic pathways and transcriptional programs to restrain proliferation and promote T cell exhaustion. Harnessing this knowledge, we demonstrate that perturbation of PBAF complex constrained exhaustion and promoted expansion of tumor-specific CD8+ T cells resulting in antitumor immunity in a preclinical melanoma model, implicating PBAF as an attractive target for cancer immunotherapeutic.